Pemanfaatan Ekstrak Kayu Manis (Cinnamomum Burmanii) dan Kulit Lemon sebagai Bahan Alami Pembuatan Footspray - Almadini, Nurul; Sari, Ratna; Amalia, Zuhra; Dewi, Ratni (Jurnal Teknologi, 2025)
Footspray is a practical alternative for maintaining foot hygiene and preventing odor caused by microbial activity in moist conditions. This study aimed to develop a natural footspray using cinnamon bark (Cinnamomum burmanii) and lemon peel (Citrus limon) extracts. Extraction was carried out by maceration with 96% ethanol, using particle sizes of 40/60, 60/80, and 80/100 mesh, and soaking times of 2-6 days. Extracts were evaluated for yield, solvent residue, flavonoid content, and antioxidant activity, then formulated into footspray with concentrations of 10-30%. The highest yield was obtained on the 5th day, with solvent residue 1%. Antioxidant activity was very strong, with IC50 values of 3.83 ppm for cinnamon and 7.14 ppm for lemon peel. Among the formulations, a 20% extract provided the best physical properties (pH, specific gravity, viscosity), strongest antibacterial effect, and highest panelist preference in organoleptic testing. These findings demonstrate that cinnamon bark and lemon peel extract are promising natural active ingredients for footspray, with 20% concentration offering optimal functional and sensory performance. This study supports the potential of natural bioactive compounds for safe, effective, and consumer-preferred foot care products.